B‐cell activating factor (BAFF), BAFF promoter and BAFF receptor allelic variants in hepatitis C virus related Cryoglobulinemic Vasculitis and Non‐Hodgkin's Lymphoma. Issue 4 (2nd May 2022) - Gragnani, Laura; Lorini, Serena; Marri, Silvia; Rattotti, Sara; Madia, Francesco; Zibellini, Silvia; Monti, Monica; Basile, Umberto; Di Stasio, Enrico; Libra, Massimo; Arcaini, Luca; Zignego, Anna Linda
Abstract: Cryoglobulinemic Vasculitis (CV) is an autoimmune/lymphoproliferative disorder associated with HCV infection that in 5%–10% of cases evolves into a B cell Non‐Hodgkin's Lymphoma (NHL). B‐cell activating factor (BAFF) is a key regulator in B‐cell development and survival. Particular genetic variants are responsible for BAFF signaling impairment in autoimmune and neoplastic diseases. We evaluated BAFF and BAFF‐receptor (BAFF‐R) polymorphisms in order to determine if they predispose to HCV‐related CV and NHL. The analysis was performed on 416 HCV‐chronically infected patients: 136 HCV without signs/symptoms of lymphoproliferations/autoimmunity (HCV), 166 HCV with CV (HCV‐CV) and 114 HCV with NHL (HCV‐NHL). Rs9514828 SNP on BAFF promoter, rs61756766 on BAFF‐R and rs12428930 on the BAFF gene were evaluated by Real‐Time PCR. Concerning rs9514828, the frequency of C/T genotype was significantly higher in HCV‐CV than in HCV. The difference in the distribution of the T/T mutant genotype in HCV‐CV compared to HCV was significant as well as the distribution of C/T and T/T genotype in HCV‐NHL versus HCV. T minor allele was more frequent in HCV‐NHL and HCV‐CV than in HCV. The distribution of C/T + T/T (for the dominant model of penetrance C/T + T/T vs. C/C) was significantly higher in HCV‐CV and HCV‐NHL than in HCV. Genotyping of rs61756766 on BAFF‐R coding gene, revealed C/T heterozygosis at a frequency of 11% in HCV‐NHL versus 3% in HCV. The T minor allele frequency was higher in HCV‐NHL than in HCV. No differences emerged by genotyping rs12428930 SNP on BAFF coding gene. Our results reinforce the hypothesis that BAFF/BAFF‐R genetic pattern has a role in the pathogenesis of HCV‐related lymphoproliferations. BAFF/BAFF‐R variants could identify a risk haplotype for HCV related CV and NHL and a BAFF/BAFF‐R genetic profile assessment could potentially contribute to tailoring anti‐BAFF therapy by identifying patients with BAFF alterations in which the treatment could be more beneficial.